Konfirmasi Index Eritrosit Dengan Sediaan Apus Darah Tepi (Sadt) Pada Penduduk Tambaklorok Semarang Yang Terpajan Pb - Santosa, Budi (Jurnal Teknologi Laboratorium, 2020)
Erythrocyte index consisting of MCV, MCH, MCHC serves for the classification of types of anemia. High or low erythrocyte index can give a picture of erythrocyte morphology in the peripheral blood smear preparation. Lead exposure in Tambaklorok exceeds the threshold that affects anemia. The purpose of this study was to determine the erythrocyte index confirmation with erythrocyte morphology in the peripheral blood smear preparation. This type of analytic research is cross sectional approach. The research population was Tambaklorok Semarang residents and 104 samples were taken using purposive technique. Erythrocyte index was measured using hematological analyzer and erythrocyte morphology in the peripheral blood smear preparation using Giemsa painting. Erythrocyte index confirmation with the peripheral blood smear preparation was analyzed using the Gamma statistical relationship test. The results showed that the erythrocyte index value was mostly in the normal category, i.e., MCH 68 (64.4%), MCHC 61 (58.6%) and MCH 58 (56%) and below normal category were MCH 45 (42.95%), MCHC 41 (39.4%), and MCV 36 (34.3%). Erythrocyte morphology was mostly hypochromic, namely 46 (44.23%), normochrome 40 (38.46%), and hyperchrome 18 (17.3%). Relationship of MCH with erythrocyte color p value 0.037 with size p value 0.038. Conclusion of erythrocyte index confirmation, especially MCH with the peripheral blood smear preparation, there was a match on the color and size of erythrocytes, while the MCV and MCHC values ​​had no significant relationship.